Dead Sea rising [large type] - Jenkins, Jerry B. (Jenkins, Jerry B. Dead Sea chronicles ;, 2018)
Nicole Berman is an archaeologist on the brink of a world-changing discovery. During her first dig in Jordan, she believes she has found concrete evidence of a biblical patriarch that could change history books forever. But someone doesn't want the truth revealed. While urgently trying to connect pieces of an ancient puzzle, a dangerous enemy is out to stop her.